« Le mal napolitain » : les Alliés et la prostitution à Naples (1943-1944) - Julie Le Gac (Genre & Histoire)
When the Allies landed in Southern Italy in September 1943, the misery engendered by years of fascism and war forced women of all ages and all social classes into prostitution. This gloomy reality, which would inspire literature, became a matter of public health for the Allied authorities, as the rate of venereal diseases rose breathtakingly, and raised the issue of the sexuality of European, American, colonial and Black American soldiers.This article analyses the representation of prostitution and the policies implemented by the American, British and French armies in order to contain the rise of venereal diseases. The wide range of solutions contemplated in the debates between physicians and officers and the wavering between principles and pragmatism reveal both the shared fear of female seduction and distinct conceptions of the soldiers’ sexuality. Furthermore, this comparison reveals distinct models of military virility in different armies